Physical mathematical modelling of difficult elements of acrobatic rock-and-roll - Adashevskiy, V. M.; Iermakov, S. S.; Firsova, Iu. Iu. (Kharkiv State Academy of Design and Arts, 2013)
It is shown directions of biomechanics substantiation of implementation acrobatic rock-and-roll Fus-salto element taking into account concrete physical data of sportsmen. Mathematical model is developed for determination the influence on a quality of implementation of technical element of such parameters as: speed and angle of flight of centre-of-mass sportsman’s body, position of centre-of-mass body of sportsman in the initial phases of throw exercises, initial angular velocity of rotation of body of sportsman. It is developed mathematical model to determine the impact on the quality of the technical element parameters such as speed and angle of flight of centre-of-mass of the athlete's body, the position of center-of-mass of the athlete's body in the initial phases of throwing exercises in the initial angular velocity of the athlete's body. The parameters of exposure axial moments of inertia for different groupings of body angular velocity the athlete's body in flight and air resistance forces of environment to flight characteristics of the body. Directions of choice of necessary biomechanics descriptions which are able to realize sportsmen are shown. It is offered recommendations are on the increase of efficiency of implementation of element of acrobatic rock-and-roll of Fus-salto.
Keywords: rock-and-roll; biomechanics; trajectory; throw